FASER (Formal and Automatic Security Enforcement by Rewriting) by BPA algebra with test. (1st January 2013) - Sui, Guangye; Mejri, Mohamed
A correct and a cheap enforcement of security policies on information systems is a major problem for most of our institutions. In previous works, we introduced a program rewriting approach that can automatically and formally enforce security policies on untrusted programs. The program and the security policy are specified as processes in an extended version of BPA (Basic Process Algebra). After that, the enforcement problem is turned to the resolution of a linear system. In this paper, we extend the expressiveness of the algebra by adding tests which is an important step towards enforcing security policies on more real interesting systems.